(3GdeNJGQ GdLGeY Hjf GdefJbi hGdGSJPcGQs - (3CHh YHO Gddg eMeO Hf YHO GdMb Hf SdjeGf GdjYaQi GdJdeSGfis
(3ChdgG (B:s
(3eGjLhR ddMQe Ccdg ef GdUjO eSCdI Yf CHj GdfVQ Yf CHj bJGOI Gfg cGf eY QShd Gddg Udi Gddg Ydjg hSde EPG cGfhG HHYV WQjb ecI JNda eY CUMGHg eMQejf hgh ZjQ eMQe s
(3BNQgG (B:s
(3eG LGA ai Gdjejef Ydi GdefHQ hCNQ GdehLhO efg hba GdeWdhH Ydi Pdc s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3GdfSNI HgG JdhjK , JQeje s
(3eUOQ GbJfGA GdCUd (B:s
(3NRGfI LGeYI GdbQhjjf HaGS (B(174 / 40) s
Keywords: (3GdMOjK h GdeUWdMs